2006
DOI: 10.1155/2006/196825
|View full text |Cite
|
Sign up to set email alerts
|

Electron paramagnetic resonance and mass spectrometry: Useful tools to detect ultraviolet light induced skin lesions on a molecular basis – A short review

Abstract: Abstract. Ultraviolet radiation is considered responsible for sunburning, premature skin aging, and cancerogenesis through the production of free radical species. Therefore, the favoured possibility for direct detection of unpaired electrons -electron paramagnetic resonance spectroscopy -is predestinated for detection and structural and dynamic analysis of this kind of molecules. However, many of UV induced radicals in skin have a short lifetime at ambient conditions and possibilities for stabilisation or tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Hence, it can be used to stud y the antioxidative activity of some compounds or extracts in the extracellular medium. Hochkirch et al 154 used EPR with Cat 1 to measure the antioxidative capacity of extracellular solu tions in human skin biopsies exposed to UV irradiation. By evaluating the decrease in the EPR signal, they showed that UV light diminishes the activity of antioxidants in the extracellular milieu.…”
Section: Evaluation Of Antioxidative Activity With Epr Spin-probingmentioning
confidence: 99%
“…Hence, it can be used to stud y the antioxidative activity of some compounds or extracts in the extracellular medium. Hochkirch et al 154 used EPR with Cat 1 to measure the antioxidative capacity of extracellular solu tions in human skin biopsies exposed to UV irradiation. By evaluating the decrease in the EPR signal, they showed that UV light diminishes the activity of antioxidants in the extracellular milieu.…”
Section: Evaluation Of Antioxidative Activity With Epr Spin-probingmentioning
confidence: 99%
“…The spatial resolution of about 10 µm is sufficient to describe the presented model systems and should be applicable to structured biological objects such as human skin. 8,15 The present paper was aimed at investigating the possibilities of ESRI with respect to the lateral diffusion of spin probes in two-phase systems, including the changes in micropolarity and microviscosity in model systems. For the interpretation of the changes in micropolarity, a simple model was developed based on the Nernst distribution law, which can also be applied to other heterogeneous or structured systems such as nanoemulsions, solid lipid nanoparticles, and last but not least to human skin.…”
Section: -13mentioning
confidence: 99%
“…Figure 13 reveals another effect, which is easily recognizable in the tomogram but much weaker in the cw spectra. With increasing concentration of the spin probe 15 N-TEMPO aggregation in the matrix Precirol occurs, causing the broad central line in the tomogram after image reconstruction.…”
Section: The System Precirol (mentioning
confidence: 99%
See 1 more Smart Citation